Analisis Pengaruh Kepuasan Pelanggan Terhadap Loyalitas Pelanggan pada Fish Streat Cabang Tebet - Nurhidayati Nurhidayati; Kartika Yuliantari (Universitas Bina Sarana Informatika, 2018)
Competition in business today is getting tougher. To attract buyers is not enough just rely on products and quality of the goods, but also required services that can provide satisfaction to customers. The hope with the satisfaction, there will be customer loyalty, and end up gaining profits in the business. This study aims to determine the effect of customer satisfaction on customer loyalty Fish Streat Branch Tebet. By using quantitative methods, data collection through observation methods, interviews, documentation and questionnaires distributed to 86 respondents. Based on questionnaires distributed to 86 respondents, obtained the results of calculation of correlation coefficient of 0.753 means shows there is a strong influence between customer satisfaction with customer loyalty. The result of calculation coefficient of determination, customer satisfaction to customer loyalty that is equal to 0,567% and the rest influenced by other factor not explained in this research. The regression coefficient test shows that Y = -3.240 + 1.219 X, indicating that there is a decrease in customer loyalty of -3.240, if customer satisfaction equal to 0 and every increase / decrease in customer satisfaction of 1, then can increase / decrease customer loyalty of 1,219 .Keywords: Customer Satisfaction, Customer Loyalty